The Social Media Marketing Mix Trends in Indonesia for 2024: Communication Perspective - Rosmawaty Hilderiah Pandjaitan (Ikatan Sarjana Komunikasi Indonesia, 2024)
Background: 86% of marketers believe social media marketing mix trends have influenced their profits. This condition significantly changes the business world and offers integrated marketing communications strategy options.This is a qualitative research in the interpretive paradigm. Using netnography or virtual ethnography or digital ethnography methods, this research attempts to explore and analyze the complex meaning of Indonesia's latest social media statistical data, compiled from We Are Social and The Global Statistics. We support data from Pew Research Center, Statista, Deloitte, Forbes, Insider Intelligence, Forrester, LinkedIn, GlobalWebIndex, CMO Survey, and the FGD (Focus Group Discussion) method. The analytical tools used are Computer-Mediated Communication Theory, Everett Rogers' Theory of Diffusion of Innovation, etc. In 2024, the social media marketing mix (SMMM) will be dominated by Artificial Intelligence (A.I.) including Generative A.I. and ChatGPT technology, as well as creative content that is entertaining and capable of attracting various kinds of people, and creates social polemics too. The principle,